An Evaluation of the Functionality of Field Study Courses in the Teacher Education Program - Bansolay, Caren Rimando (IJRDO- Journal of Educational Research, 2018)
This study aimed to determine the functionality of the field courses in compliance with the standards set by the seven identified areas of evaluation, namely: institutional VMGO, administration, supervision of instruction, faculty eligibility, pedagogical principles, curriculum and learning competencies. It also intended to identify the problems encountered by students and teachers that influence the degree of functionality of field study courses in the teacher education program of the institution.            Findings revealed that in general, the degree of functionality of the field study courses in compliance with the minimum standards set by the seven identified areas of evaluation is operational, with areas identified as compliant but not functional, and functional but not compliant. It is only in the areas of institutional VMGO and the supervision of instruction that the functionality of the field courses is found fully operational. The administration, faculty eligibility, pedagogical principles, curriculum and learning principles are operational. Thus, the assumption on the connectivity of the operation and implementation of educational programs in the teacher education program to that of the existing educational functions is strengthened.             The problems were summarized into five general categories. For the students, deficient time for field study observation, difficulty in dealing with the cooperating teacher and the supervising teacher, FS student observer as substitute of the FS cooperating teacher, difficulty in adjusting to actual classroom instruction, and lack of communication on matters what to do, what to submit and when to submit, were their major problems. For FS teachers, on the other hand, deficient time for field study orientation, difficulty in dealing with the cooperating schools, scarcity of references, overloading, and unclear, inefficient, inadequate implementation guidelines were their problems. Both the students and the teachers identified inadequate time as their first major problem, and they were aware that these problems are recursive in nature.